MICROSERVICE ARCHITECTURE VS MONOLITHIC: AN ANALYSIS IN DEVELOPING SCALABLE SOLUTIONS - Azizyan L.V. (Modern American Journals, 2025)
With today's digital systems growing bigger and reaching more people, how software is structured has become really important for keeping things running smoothly over time. This paper looks at the differences between building software as one big piece (monolithic) versus breaking it down into smaller, independent services (microservices). We're focusing on how these choices affect whether the system can handle more users, how easy it is to update and fix, and the ways you can put new versions into action. By looking at actual examples and sharing practical lessons, we show how each method fits different company needs as they grow. The goal of this study is to help people make smart choices by looking at the give-and-take in speed, reliability, and how quickly development teams can move in different business and tech situations.